2021
DOI: 10.3390/cryst11030320
|View full text |Cite
|
Sign up to set email alerts
|

Processability and Optimization of Laser Parameters for Densification of Hypereutectic Al–Fe Binary Alloy Manufactured by Laser Powder Bed Fusion

Abstract: Centimeter-sized samples of hypereutectic Al–15 mass% Fe alloy were manufactured by a laser powder bed fusion (L-PBF) process while systematically varying laser power (P) and scan speed (v). The effects on relative density and melt pool depth of L-PBF-manufactured samples were investigated. In comparison with other Al alloys, a small laser process window of P = 77–128 W and v = 0.4–0.8 ms−1 was found for manufacturing macroscopically crack-free samples. A higher v and P led to the creation of macroscopic crack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 56 publications
(119 reference statements)
0
4
0
1
Order By: Relevance
“…As a result, it was found that the arrangement of P and v based on the deposited energy density 18) , which takes into account the thermal diffusion length in solid parts, is more effective for densification of the maraging steel samples (rather than the commonly used volumetric energy density 19) ). It was confirmed that the approach was vailed to different alloy systems 20,21) as well. The search for optimum conditions in the L-PBF process has identified a range of P and v for manufacturing maraging steel samples with relative densities above 99% 17) .…”
Section: Introductionmentioning
confidence: 68%
“…As a result, it was found that the arrangement of P and v based on the deposited energy density 18) , which takes into account the thermal diffusion length in solid parts, is more effective for densification of the maraging steel samples (rather than the commonly used volumetric energy density 19) ). It was confirmed that the approach was vailed to different alloy systems 20,21) as well. The search for optimum conditions in the L-PBF process has identified a range of P and v for manufacturing maraging steel samples with relative densities above 99% 17) .…”
Section: Introductionmentioning
confidence: 68%
“…The large lattice parameters of the α-Al phase in the L-PBF-built Al-15%Fe samples were presumably due to the presence of O solute atoms positioned at interstitial sites in the fcc structure. Composition analyses [20,21] have revealed that the alloy powder contains ~0.25-0.3 mass% O, which indicates that a thin oxide layer is present on the investigated alloy powder particles. These oxide films could dissolve in the alloy melts during L-PBF.…”
Section: Changes In α-Al Matrix At Elevated Temperaturesmentioning
confidence: 95%
“…An Al-15Fe (mass%) binary alloy powder with an average particle size below 30 µm was prepared via gas atomization; the details concerning the preparation of the alloy powder can be found elsewhere [20]. Rectangular samples with the approximate dimensions of 15 × 15 × ~5 mm 3 were constructed using a ProX DMP 200 machine (3D Systems, Rock Hill, SC, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…従来の加工法では不可能な三次元複雑形状の造形を可能 とした [1][2][3][4] 。積層造形技術を用いた材料の造形プロセスは, 3D プリンティングやアディティブ・マニュファクチャリ ング(Additive Manufacturing)と称される場合も多い 3) 。金 属材料に適用される積層造形技術で最も汎用的なプロセ スのひとつは,レーザ粉末床溶融結合(Laser Powder Bed Fusion: L-PBF)法 [1][2][3][4][5] である。不活性ガス雰囲気中のチャ ンバー内に敷設した金属粉末を 1 層ずつ積層し,造形部に レーザ照射し溶融・凝固を繰り返し,構造体を造形する。 この L-PBF プロセスは鉄鋼材料の複雑形状部材の造形を可 能とし,軽量構造部材だけでなくプレス・射出成形用の金 型等への適用が期待されている。鉄鋼材料の合金粉末を用 いた L-PBF プロセス [6][7][8] は SUS316L 9,10) ,SUS304L 10) やマル エージング鋼 11,12) にて多く報告されているが,近年では二 相ステンレス鋼 13) ,17-4PH 14) (SUS630 相当) ,工具鋼 15) や 高強度鋼 16) など幅広い材料への適用が報告されている。 これまで,任意の形状を有するマルエージング鋼金型 の L-PBF 法を用いた積層造形の実現を見据え,緻密な造形 体作製に最適なレーザ条件の探索を目的とし,マルエー ジング鋼造形体の相対密度に及ぼす L-PBF プロセス条件 (レーザ出力 P とレーザ走査速度 v)の影響を系統的に調査 した 17) 。その結果,一般に用いられる体積エネルギー密度 (Volumetric energy density) 18) より,材料中の熱拡散長を考 慮した Deposited energy density 19) に基づく P と v の整理が, マルエージング鋼造形体の緻密化に有効であることを見出 した 17) 。この整理は,アルミニウム合金等の他の金属材料 にも有効であることが検証されている 20,21) 。L-PBF プロセ スにおける最適条件の探索は,99%以上の相対密度を持つ マルエージング鋼造形体の製造可能な P と v の範囲を同定 した 17) 。異なる条件(P,v)で造形したマルエージング鋼の 組織を予備的に調査した結果,いずれの造形体もマルテン サイト組織内部に微細な残留オーステナイト(γ)相が存在 することを明らかにした 22) 。これは,他の研究報告 23,24) と 一致する。また,残留 γ 相の体積率は,P と v によって変化 することも見出した。この L-PBF プロセス条件による残留 γ 相の変化は,その後の熱処理に伴うオーステナイト逆変 態に大きく影響を及ぼすと考えられ,プロセスを利用した 逆変態制御によるマルエージング鋼造形体の高強度・高延 性化 25) が期待される。これまで,L-PBF プロセスによるマ ルエージング鋼積層造形体の微細な金属間化合物相の析出 11,26,27) や熱処理に伴う機械的性質の変化 11,12,25,28) に関する研 究報告は多いが,オ...…”
Section: 近年,積層造形(付加製造)技術は飛躍的な発展を遂げ,unclassified